Perilipin 1 Mediates Lipid Metabolism Homeostasis and Inhibits Inflammatory Cytokine Synthesis in Bovine Adipocytes - Zhang, Shiqi; Liu, Guowen; Xu, Chuang; Liu, Lei; Zhang, Qiang; Xu, Qiushi; Jia, Hongdou; Li, Xiaobing; Li, Xinwei (Frontiers in Immunology, 2018)
Dairy cows with ketosis displayed lipid metabolic disorder and high inflammatory levels. Adipose tissue is an active lipid metabolism and endocrine tissue and is closely related to lipid metabolism homeostasis and inflammation. Perilipin-1 (PLIN1), an adipocyte-specific lipid-coated protein, may be involved in the above physiological function. The aim of this study was to investigate the role of PLIN1 in lipid metabolism regulation and inflammatory factor synthesis in cow adipocytes. The results showed that PLIN1 overexpression upregulated the expression of fatty acid and triglyceride (TAG) synthesis molecule sterol regulator element-binding protein-1c (SREBP-1c) and its target genes, diacylglycerol acyltransferase (DGAT) 1, and DGAT2, but inhibited the expression of lipolysis enzymes hormone-sensitive lipase (HSL) and CGI-58 for adipose triglyceride lipase (ATGL), thus augmenting the fatty acids and TAG synthesis and inhibiting lipolysis. Importantly, PLIN1 overexpression inhibited the activation of the NF-κB inflammatory pathway and decreased the expression and content of tumor necrosis factor alpha (TNF-α), interleukin 1 beta (IL-1β), and interleukin 6 (IL-6) induced by lipopolysaccharide. Conversely, PLIN1 silencing inhibited TAG synthesis, promoted lipolysis, and overinduced the activation of the NF-κB inflammatory pathway in cow adipocytes. In ketotic cows, the expression of PLIN1 was markedly decreased, whereas lipid mobilization, NF-κB pathway and downstream inflammatory cytokines were overinduced in adipose tissue. Taken together, these results indicate that PLIN1 can maintain lipid metabolism homeostasis and inhibit the NF-κB inflammatory pathway in adipocytes. However, low levels of PLIN1 reduced the inhibitory effect on fat mobilization, NF-κB pathway and inflammatory cytokine synthesis in ketotic cows.